Microstructure and mechanical properties of electroplated Ni-Sn TLP bonded joints with different bonding and aging times - Yan, Guangxu (2023)
Much attention has been drawn to the Ni-Sn transient liquid phase (TLP) bonded joints for high-temperature electronic packaging applications since their inception. A comparative study of Ni-Sn TLP bonded joints with different interlayers was conducted. The evolution of microstructure and mechanical properties of joints with different bonding times was also investigated. In addition, the high-temperature (300 °C) thermal reliability of the Ni-Sn TLP bonded joints was explored with aging times from 0 h to 100 h. The results show that electroplated Ni-Sn TLP bonded joints exhibited a slightly higher average shear strength than those prepared using Sn foil and Sn96.5Ag3.5 paste. Also, the average shear strength of the electroplated Ni-Sn TLP bonded joints was greatly improved when the bonding time increased from 0.5 h to 5 h, while there was a continuous decrease in the average shear strength as the aging time was increased from 4 h to 100 h. During aging, the Ni/Ni3Sn2 interface was the preferential site for the nucleation of newly formed Ni3Sn2 intermetallic compounds (IMCs). Furthermore, the cross-sectional microstructure of the shear fractured joints after aging from 4 h to 100 h indicates that the shear fractures propagated through both the Ni3Sn4 IMCs and the Ni3Sn2/Ni3Sn4 interface.